The Relationship Between Compliance With The Use Of Personal Protective Equipment (PPE) And The Rate Of Needle Injury Incidents Stick Injuries In Clinical Practice Students - Nurnainah Nurnainah; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
Needle stick Needlestick injuries (NSIs) are a common occupational risk among healthcare workers and clinical practice students. Needlestick injuries can lead to the transmission of infectious diseases such as Hepatitis B, Hepatitis C, and HIV. One way to prevent NSIs is compliance with the use of Personal Protective Equipment (PPE) during clinical procedures. This study aims to determine the relationship between compliance with PPE use and the incidence of needlestick injuries. stick injury in clinical practice students. This study used a quantitative method with an analytical design and a cross-sectional approach. The study was conducted in a sectional manner. The sample of the study was students undergoing clinical practice at practice area X. Data were collected using a questionnaire and analyzed using the Chi- Square test. The results of the study showed a significant relationship between compliance with the use of PPE and the incidence of needle sticks. stick injury (p < 0.05). The conclusion of this study is that students who do not comply with the use of PPE have a higher risk of experiencing needle sticks. stick injury.